Empowerment of Sekar Jepun VCO KWT to Increase Production and Business Capacity in Penglipuran Village, Bangli Regency - L.G.P Sri Eka Jayanti; I Ketut Selamet; A. A. Sri Purnami (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2026)
Virgin Coconut Oil (VCO) is a processed coconut product with high economic value and is widely used in the health, beauty, and food sectors. One VCO business group in Bangli Regency is the Sekar Jepun VCO Women Farmers Group (KWT) located in Penglipuran Village. This KWT has significant potential in developing local product-based businesses, but still faces various obstacles such as limited business management, rudimentary financial records, limited access to capital, and minimal use of digital marketing. To address these issues, community service activities were designed through participatory-based training and mentoring programs. These activities aimed to improve the knowledge and skills of group members in business management and digital marketing. The implementation method was carried out through socialization, training, practice, and direct mentoring related to creating simple bookkeeping, preparing credit application proposals, and utilizing social media as a digital marketing tool. The results of the activities showed an increase in participants' understanding of business management and digital marketing. The average score for understanding business management increased to 3.06 and digital marketing increased to 3.13 after mentoring. This program has a positive impact on improving the group members' abilities in managing their businesses professionally and expanding the marketing of VCO products through digital media.